Increased oxygen uptake in well-trained runners during uphill high intensity running intervals: A randomized crossover testing - Held, Steffen; Rappelt, Ludwig; Giesen, René; Wiedenmann, Tim; Deutsch, Jan-Philip; Wicker, Pamela; Donath, Lars (Frontiers in Physiology, 2023)
The time spent above 90% of maximal oxygen uptake (V̇O2max) during high-intensity interval training (HIIT) sessions is intended to be maximized to improve V̇O2max. Since uphill running serves as a promising means to increase metabolic cost, we compared even and moderately inclined running in terms of time ≥ 90% V̇O2max and its corresponding physiological surrogates. Seventeen well-trained runners (8 females & 9 males; 25.8 ± 6.8yrs; 1.75 ± 0.08m; 63.2 ± 8.4kg; V̇O2max: 63.3 ± 4.2ml/min/kg) randomly completed both a horizontal (1% incline) and uphill (8% incline) HIIT protocol (4-times 5min, with 90s rest). Mean oxygen uptake (V̇O2mean), peak oxygen uptake (V̇O2peak), lactate, heart rate (HR), and perceived exertion (RPE) were measured. Uphill HIIT revealed higher (p ≤ 0.012; partial eta-squared (pes) ≥ 0.351) V̇O2mean (uphill: 3.3 ± 0.6 vs. horizontal: 3.2 ± 0.5 l/min; standardized mean difference (SMD) = 0.15), V̇O2peak (uphill: 4.0 ± 0.7 vs. horizontal: 3.8 ± 0.7 l/min; SMD = 0.19), and accumulated time ≥ 90% V̇O2max (uphill: 9.1 ± 4.6 vs. horizontal: 6.4 ± 4.0 min; SMD = 0.62) compared to even HIIT. Lactate, HR, and RPE responses did not show mode*time rANOVA interaction effects (p ≥ 0.097; pes ≤ 0.14). Compared to horizontal HIIT, moderate uphill HIIT revealed higher fractions of V̇O2max at comparable perceived efforts, heartrate and lactate response. Therefore, moderate uphill HiiT notably increased time spent above 90% V̇O2max.